Rectal Spacer Reduces Gastrointestinal Side Effects of Radiation Post Radical Prostatectomy - Anne Hong; Damien Bolton; Trung Pham; David Angus; David Pan; Daryl Lim Joon; Alwin Tan; Kevin McMillan; Yee Chan; Paul Manohar; Joe Thomas; Huong Ho; et al. (Société Internationale d’Urologie Journal)
Objectives: Our objective was to assess the rate of complications and gastrointestinal adverse effects of rectal spacer insertion for salvage post prostatectomy radiation therapy. Methods: A retrospective observational study was performed. Between September 2018 and March 2022, 64 post-radical prostatectomy patients who were planned for salvage radiation therapy received a rectal spacer. The selected patients were those who had nerve-sparing prostatectomy with intrafascial or interfascial dissections (where Denonvillier’s fascia is retained). Radiation dose to the rectal wall and gastrointestinal symptoms were assessed. Symptoms were graded using the National Cancer Center Institute Common Terminology Criteria for Adverse Events v4.0 grading scheme. A total of 39 patients had pre-spacer planning computer tomography (CT) scans, and the rectal dose before and after the spacer insertion was calculated. Comparisons were made using the Student’s t-test, with a p-value < 0.05 representing statistical significance. Finally, clinicians were surveyed to rate the ease of the procedure using a 5-point Likert scale of 1 to 5 (1: very difficult, 2: difficult, 3: moderate, 4: easy, 5: very easy). Results: A total of 64 patients successfully underwent rectal spacer insertion. The mean age was 64.4 years (standard deviation: 5.7 years). After a median of 14 months’ (range 6 to 35) follow up, acute grade 1 and above gastrointestinal (GI) toxicities were seen in 28% of patients (grade 2 in 1.5%), and late grade 1 and above GI toxicities were seen in 12% of patients (grade 2 in 1.5%). Amongst the 39 patients with pre-spacer planning CT images, the volume of the rectum receiving 60%, 70%, 80%, 90%, and 100% of the prescribed radiation dose was reduced by 25.9%, 34.2%, 35.4%, 43.7%, and 61.7%, respectively. All dose reductions were statistically significant. The procedure was rated as “easy” or “very easy” to perform in 56% of cases. Conclusions: The insertion of a rectal spacer in selected patients undergoing PPRT is feasible and safe and significantly improves rectal wall radiation dosimetry in salvage post prostatectomy radiation therapy. It was accomplished in >95% of patients, increasing vesico-rectal separation from ‘immediate vicinity’ to 11 mm without any post-operative complications in experienced hands. In addition, it achieved significant reduction in rectal radiation doses, leading to low rates of acute and late grade 2 toxicity.